Gender Issues in the Micro, Small, and Medium Enterprise Sector in India - International Center for Research on Women (World Bank, Washington, DC, 2017)
Micro, small, and medium enterprises (MSMEs) are an important instrument of growth for India’s economy. The contribution of the MSME sector to India’s gross domestic product (GDP) was estimated to be around 8 to 9 percent in 2012 after agriculture; MSMEs have emerged as the second largest source of employment in India. For growth to be inclusive and equitable, it is critical to understand how to enhance the role of women in the economy and in particular in the MSME sector. In order to fill the gap, the World Bank has commissioned International Centre for Research on Women (ICRW), Asia Regional Office, New Delhi to conduct a short, field based assessment of gender issues in MSMEs in India. The study involved field-based assessment of gender related issues in select MSME clusters to identify challenges and opportunities for inclusion of women in higher numbers and at higher levels of growth in the MSME sector. The study findings will ultimately be operationalized into a Bank-supported MSME project in India and help inform Government of India policy on more inclusive growth of the MSME sector, especially towards strengthening gender equality and economic empowerment of women in the sector.